2009
DOI: 10.1007/s00248-009-9542-8
|View full text |Cite
|
Sign up to set email alerts
|

Benthic ecology of Vibrio spp. and pathogenic Vibrio species in a coastal Mediterranean environment (La Spezia Gulf, Italy)

Abstract: We carried out a 16-month in situ study to investigate the ecology of Vibrio spp. and pathogenic Vibrio species in coastal sediments of the Mediterranean Sea, employing multiple-regression analysis to reveal the major environmental factors controlling their occurrence in the benthic environment. In addition, association between vibrios and sediment-inhabiting meiofauna, which is a major component of benthic ecosystems, was investigated. Culturable and total Vibrio spp. estimates by most-probable-number techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(109 citation statements)
references
References 28 publications
10
90
1
1
Order By: Relevance
“…Although previous studies in different regions showed that sediments can harbour high amounts of Vibrio spp. [12,40,63,64], such a high difference in the number of viable cells between sediment and water seems to be extraordinary. The possibility of an active benthic lifestyle of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies in different regions showed that sediments can harbour high amounts of Vibrio spp. [12,40,63,64], such a high difference in the number of viable cells between sediment and water seems to be extraordinary. The possibility of an active benthic lifestyle of Vibrio spp.…”
Section: Discussionmentioning
confidence: 99%
“…[15]), few environmental studies have considered the sedimentary matrix (e.g. [39,40]), thus neglecting an important component with regard to the assessment of possible health risks.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, negative correlations have also been described between temperature and total vibrios in the waters of India (46,67) and Louisiana (68). Temperature has also been positively correlated to total vibrios in mussels (59) and sediment (47,64,69). A 2003 study identified a distinct temperature effect when Vibrio coralliilyticus infected the coral Pocillopora damicornis; V. coralliilyticus pathology was higher at 27°C and 29°C than at 25°C (70).…”
Section: Other Vibriosmentioning
confidence: 99%
“…Although these studies have not focused on the top three human pathogens, they are important because they shed light on the ecology of naturally occurring vibrios and because of the relationships with pathogens with which they may exchange genetic material. Positive relationships have been described between temperature and total vibrios in the waters of Germany (58,59), North Carolina (31,55,60,61), the country of Georgia (62), the state of Georgia (63), Italy (64,65), South Africa (66), and Germany (47). Interestingly, negative correlations have also been described between temperature and total vibrios in the waters of India (46,67) and Louisiana (68).…”
Section: Other Vibriosmentioning
confidence: 99%
“…Environmental parameters, such as temperature, salinity or plankton abundance have an effect on Vibrio spp. communities and abundances (Blackwell and Oliver, 2008;Caburlotto et al, 2010;Drake et al, 2007;Martinez-Urtaza et al, 2008;Thompson et al, 2004b;Turner et al, 2009;Vezzulli et al, 2009). Vezzulli et al (2010) and Schets et al (2010) identified seawater temperature as a key factor influencing the presence of Vibrio spp., for instance it is well documented that V. parahaemolyticus favours warmer water temperatures (Sobrinho et al, 2010).…”
Section: Vibrio Hitchhikersmentioning
confidence: 99%